Implementasi Menu Sehat Anti Anemia untuk Remaja Panti Asuhan Aisyiyah Kudus - Purbowati; Septiani; Fania Nurul Khoirunnisa; Maya Eka Mutiara; Sabila Rizqy Fauziah; Zhahira Haura Nasywa (UNIVERSITAS NGUDI WALUYO, 2024)
Adolescent girls are susceptible to anemia. This is because the body experiences rapid growth, high physical activity and menstruation begins so that the body requires a high intake of nutrients, especially protein and iron. If iron needs are not met it can cause anemia. The Aisyiyah Kudus Orphanage accommodates 43 teenage girls aged 10-19 years. Daily food intake is provided by the orphanage which organizes food on a self-managed basis, with a 7 day menu cycle with 3 meal times. However, the menu provided is less balanced, especially the breakfast menu which does not contain vegetables and lacks animal side dishes. Limited budget and cooking power, as well as children's appetites that don't like vegetables, are factors causing the presentation of this menu. Training on preparing healthy menus for managers and youth anemia education for children in orphanages is carried out to improve the skills of managers in preparing healthy menus, serving them practically, and in accordance with the budget, as well as increasing teenagers' understanding of anemia and how to prevent it, so that they can consume healthy food menus that orphanage provided. The methods used are lectures, discussions and demonstrations. Activities were carried out for two days in the Aisyiyah Kudus Orphanage Hall. After participating in the activity, the participants' level of knowledge about anemia increased. Apart from that, there has also been an increase in managers' skills in preparing menus and making processed animal side dishes. It is necessary to monitor and evaluate the implementation of the new menu that has been prepared and its acceptance by orphanage youth. ABSTRAK Remaja perempuan rentan mengalami anemia. Hal tersebut karena tubuh remaja mengalami pertumbuhan pesat, aktivitas fisik tinggi dan mulai terjadi mestruasi sehingga tubuh membutuhkan asupan zat gizi terutama protein dan zat besi yang tinggi. Jika kebutuhan zat besi tidak terpenuhi dapat menyebabkan anemia. Panti Asuhan Aisyiyah Kudus menampung 43 remaja putri yang berusia 10-19 tahun. Asupan makan sehari-hari disediakan oleh panti asuhan yang melakukan penyelenggaraan makanan secara swakelola, siklus menu 7 hari 3 kali waktu makan. Akan tetapi menu yang disediakan kurang seimbang terutama menu makan pagi yang tidak ada sayur dan kurang lauk hewani. Keterbatasan anggaran dan tenaga masak, serta selera makan anak tidak suka sayur menjadi faktor penyebab penyajian menu tersebut. Pelatihan penyusunan menu sehat untuk pengelola dan edukasi anemia remaja untuk anak panti asuhan dilakukan meningkatkan ketrampilan pengelola dalam menyusun menu sehat, praktis penyajiannya, dan sesuai dengan anggaran belanja, serta juga meningkatkan pemahaman remaja tentang anemia dan cara mencegahnya, sehingga dapat mengkonsumsi menu makanan sehat yang disediakan panti asuhan. Metode yang digunakan yaitu ceramah, diskusi, dan demostrasi. Kegiatan dilaksanakan selama dua hari di Aula Panti Asuhan Aisyiyah Kudus. Setelah mengikuti kegiatan, tingkat pengetahuan peserta tentang anemia meningkat. Selain itu juga terjadi peningkatan ketrampilan pengelola dalam menyusun menu dan membuat olahan lauk hewani. Perlu dilakukan monitoring dan evaluasi penerapan menu baru yang telah disusun dan daya terima oleh remaja panti.